Efeitos da adição da cal hidratada na estabilização de um solo sedimentar para pavimentação urbana na região de Curitiba - Bordignon, Vitor Reinaldo (2015)
Urban paving is of paramount importance for a city, both socioeconomic and in quality of life. The urban flooring not different so-called road surface are constituted by a set of horizontal layers, overlaid on the ground, which have the main function of supporting the actions induced by the vehicle redistributing the stresses transmitted to the ground. Soils are important materials for the execution of paving, mainly because they are part of the basic structure of the floor and mostly be available in abundance, with a very low cost, however, their properties usually do not meet the requirements necessary to perform the floor. The soil stabilization for the implementation of urban pavement bases and sub-bases is an increasingly important aspect in the current situation, because always there is the concern with the environment, and there is now the clear awareness that every effort should be made to minimize the effects caused by the exploitation of deposits and deposition of material. In this sense this work presents the effects of adding different proportions of lime to stabilize a sedimentary soil sample from the urban area of the city of Curitiba. It selected a sample quantity of soil in the region to study the stabilization insertion of hydrated lime type (CHIII) powder. The two variables in the study are related to the content of lime mixed with the soil at 0% percentages of 3%, 6%, 8% and 16%, and cure times at which these mixtures were subjected to (0, 7, 14, 28 and 56 days). The tested mixtures were prepared from dosages defined by two methods: one checking the chemical behavior of the samples by means of changes in pH values, and the second analyzing the mechanical behavior through the RCS values. It has been found that the chemical stability analyzed by addition of lime, provided an average increase of RCS in most soil samples studied, because of some physical and chemical characteristics thereof. For mixtures with 6%, 8% and 16% of lime after 28 days of curing, the average RCS was 0,57 MPa, 1,06 MPa and 2,37 MPa, respectively, for the normal proctor, and as for intermediate proctor, in the same curing time and on the same percentages RCS results were 0,54 MPa, 1,04 MPa and 2,71 MPa, respectively. In global terms, the soil-lime mixtures studied showed acceptable behavior by law to use as layers of sub-base. However, only the mixture with 16% of lime, at 28 days, is recommended for use on floors bases. Even so, the mixtures studied constitute a good alternative economic and socio-environmental.